2003
DOI: 10.1172/jci18817
|View full text |Cite|
|
Sign up to set email alerts
|

Complement C5a receptors and neutrophils mediate fetal injury in the antiphospholipid syndrome

Abstract: Antiphospholipid syndrome (APS) is defined by recurrent pregnancy loss and thrombosis in the presence of antiphospholipid (aPL) Ab's. Currently, therapy for pregnant women with APS is focused on preventing thrombosis, but anticoagulation is only partially successful in averting miscarriage. We hypothesized that complement activation is a central mechanism of pregnancy loss in APS and tested this in a model in which pregnant mice receive human IgG containing aPL Ab's. Here we identify complement component C5 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
375
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 329 publications
(394 citation statements)
references
References 50 publications
11
375
1
7
Order By: Relevance
“…In previous studies from our group, the findings suggested that C3 activation is required for (4). Subsequently, Girardi et al showed that complement activation, specifically C5a-C5aR interaction, is required for aPL-induced pregnancy loss and suggested that C5a promotes neutrophil infiltration of decidual tissue (5). Evidence that neutrophils activated by C5a release procoagulant substances and that monocytes activated by C5a release tissue factor suggests that infiltrating leukocytes stimulated by complement split products can initiate placental infarction and ultimately cause fetal death (8).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In previous studies from our group, the findings suggested that C3 activation is required for (4). Subsequently, Girardi et al showed that complement activation, specifically C5a-C5aR interaction, is required for aPL-induced pregnancy loss and suggested that C5a promotes neutrophil infiltration of decidual tissue (5). Evidence that neutrophils activated by C5a release procoagulant substances and that monocytes activated by C5a release tissue factor suggests that infiltrating leukocytes stimulated by complement split products can initiate placental infarction and ultimately cause fetal death (8).…”
Section: Discussionmentioning
confidence: 70%
“…Passive transfer of IgG from aPL-positive sera (IgG-APS) has been found to induce fetal loss, thrombosis, and endothelial cell activation in mice, suggesting a direct pathogenic role of aPL (1)(2)(3). Complement activation is a necessary intermediary event in the pathogenesis of fetal loss associated with aPL in this model (4,5).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Although the pathogenesis of this syndrome had been attributed to the ability of these Abs to directly modify clotting-related activities or cell activation (34), using a murine model of aPL syndrome in which pregnant mice are injected with human aPL Ab-containing IgG Abs, it was found that inhibition of the complement cascade in vivo using the C3 convertase inhibitor Crry-Ig, or using mice deficient in complement C3, resulted in the absence of fetal loss and growth retardation (35). In a subsequent study, the authors demonstrated that several factors are necessary for the development of disease in this model, including C4, factor B, C5a, and neutrophils (21). Interestingly, the depletion of neutrophils prevented C3 deposition in the deciduas, perhaps because infiltrating neutrophils (initially recruited by classical pathway activation) fuel complement activation by releasing alternative pathway components.…”
Section: Antiphospholipid (Apl) Ab Syndromementioning
confidence: 94%
“…It may be that the initial insult induces deficiencies of regulatory proteins in necrotic cells or regions of injury, setting the stage for amplification of injury by the alternative pathway. Alternatively, infiltrating cells such as neutrophils bring in C3 and properdin that increase activation specifically at that site by providing additional substrate for the alternative pathway (21). It may also be that the amplification loop is much more robust in vivo than previously appreciated.…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 99%